2020
DOI: 10.2196/16546
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Willingness to Share Information in Online Patient Communities: Questionnaire Study

Abstract: Background Online patient communities provide new channels for users to access and share medical information. In-depth study of users’ willingness to share information in online patient communities is of great significance for improving the level of information sharing among the patient community and the long-term development of communities. Objective The aim of this study was to build a model of factors affecting patients’ willingness to share medical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
1
17
2
2
Order By: Relevance
“…Although the P value is at the .1 level, the negative effect of information support on the privacy concerns is a valuable finding that supports the hypotheses [79]. However, we find that emotional support has no direct moderation effect on either privacy concerns or health information disclosure intention.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Although the P value is at the .1 level, the negative effect of information support on the privacy concerns is a valuable finding that supports the hypotheses [79]. However, we find that emotional support has no direct moderation effect on either privacy concerns or health information disclosure intention.…”
Section: Resultssupporting
confidence: 66%
“…Furthermore, informational support will have a negative moderation effect on the relationship between privacy concerns and health information disclosure (beta path coefficient –0.105, P =.092). Although the P value is at the .1 level, the negative effect of information support on the privacy concerns is a valuable finding that supports the hypotheses [ 79 ]. However, we find that emotional support has no direct moderation effect on either privacy concerns or health information disclosure intention.…”
Section: Resultsmentioning
confidence: 56%
“…14 Despite the potential benefits of sharing self-generated health and lifestyle data with others, a number of barriers have been identified that prevent the acceptance of these data-sharing practices. For instance, as electronic health data become increasingly integrated into healthcare systems, there is an increased potential for privacy breaches and misrepresentation, negatively influencing end-user trust 20 In this research we will discuss concerns surrounding concepts of Trust, Identity, Privacy and Security (TIPS) adopted from research into privacy and security perspectives. 21 TIPS concerns play an important role in facilitating sharing of health data via technology applications.…”
Section: Introductionmentioning
confidence: 99%
“…Health information sharing is one of the most important aspects in the research area of information sharing. Zhu et al [ 9 ] established an influencing factor model of patients’ willingness to share health information. The model includes variables of privacy concerns, online information support, information sensitivity, and disease severity.…”
Section: Introductionmentioning
confidence: 99%